Electrification of short sea shipping in Scandinavia - The influence on electrifying ferries within short sea shipping in the Scandinavian countries - Gullbring, Jonathan; Pandic, Anja (My University, 2021)
For many years in history, the maritime sector has propelled ferries using fossil fuels which have led to great carbon emissions, among others. This bachelor thesis is focused on the fossil-free fuel of the future, electricity. In addition, the thesis will investigate the international and national conventions which affects the development of electric ferries. The thesis has been limited to short sea shipping in the Scandinavian countries and investigates at how these countries could differ when it comes to the development of electric ferries. The work has been carried out as a comparative systematic literature study including a semi-structured interview method. The research questions cover the extent of electric ferries, different incitements to manage the development of electrifying ferries as well as the national and international conventions. Based on the interviews that were held with companies from the Swedish shipping industry, a depper research could be conducted. There are several challenges when it comes to converting to electric propulsion such as the distance between the operating ports, the possibility of charging the batteries and finding an electricity network with enough capacity. Conventions from the International Maritime Organization and the European Union have been considered as the most important influence, which also has a big influence to create national laws and regulations. The International Maritime Organization is a part of the United Nations that is focusing One conclusion that can be taken from the research is that the development of electric propulsion in short sea shipping are an important and necessary development. The development includes multiple beneficial incitements but requires a lot as well. A consideration every company and country must make. During our research, we discovered that although Scandinavia is seen to be at the forefront when it comes to the development of electric solutions for ferries the number of projects is relatively small. Companies in Norway and Denmark who are currently working on developing electric solutions for ferries did unfortunately not have time or the possibility to participate in any interviews and therefore the report was limited to interview Swedish companies.
Keywords: Electric ferries; electrified shipping; emissions; sustainability; sustainability goals; reducing emissions; short sea shipping; Sweden; Norway; Denmark